THE EFFECTIVENESS OF LAW NUMBER 6 OF 2014 CONCERNING VILLAGE IN RELATIONSHIP WITH COMMUNITY PARTICIPATION - Nelwan Nelwan (SEAN Institute, 2021)
This study aims to determine how the application and the extent to which the factors that influence Law Number 6 of 2014 concerning Villages are related to the participation of the people of Bojo Village, Budong-budong District, Central Mamuju Regency. The research method used is